2005
DOI: 10.1021/om050182b
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Phosphine/Diimine Complexes:  Syntheses, Characterization, Reactivity with Carbon Monoxide, and Catalytic Hydrogenation of Ketones

Abstract: The cis-[RuCl2(PPh3)2(N−N)] (N−N = bipy (1), Me-bipy (2), phen (3), and bathophen (4)) complexes were used to synthesize five new electron-rich phosphine-containing complexes cis-[RuCl2(dcype)(N−N)] (N−N = bipy (1a), Me-bipy (2a), phen (3a), and bathophen (4a)) and cis-[RuCl2(PEt3)2(bipy)] (1c) by phosphine exchange. These complexes were obtained and characterized by NMR (31P{1H}, 1H), cyclic voltammetry, and elemental analysis. Electrochemical studies of these complexes reveal a single reduction process (RuII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 66 publications
4
18
0
Order By: Relevance
“…The bond distances and angles listed in Table 2 are in the range expected for ruthenium diphosphine complexes. 7,[12][13][14][29][30][31][32] Similar behavior was observed for the complexes containing 4-methylpyridine and 4-phenylpyridine, as previously reported. 7,29,30 In all three complexes, the dissociated chloride was always the one trans to a phosphorus atom in the precursor cis-[RuCl 2 (P-P) (bipy)], as expected, given the stronger trans effect of the phosphorus atom and in accordance with the X-ray structures.…”
Section: Resultssupporting
confidence: 79%
“…The bond distances and angles listed in Table 2 are in the range expected for ruthenium diphosphine complexes. 7,[12][13][14][29][30][31][32] Similar behavior was observed for the complexes containing 4-methylpyridine and 4-phenylpyridine, as previously reported. 7,29,30 In all three complexes, the dissociated chloride was always the one trans to a phosphorus atom in the precursor cis-[RuCl 2 (P-P) (bipy)], as expected, given the stronger trans effect of the phosphorus atom and in accordance with the X-ray structures.…”
Section: Resultssupporting
confidence: 79%
“…In the 1 H NMR spectra, the integrals indicated a dpa: PR 3 ratio of 1:1. HMBC 1 H- 31 P experiments showed that in both complexes the PR 3 ligand is in the trans position relative to a nitrogen atom of the 2,2 0 -dipyridylamine ligand, due to the presence of coupling of one o-H with the PR 3 ligand as described elsewhere [23]. These observations are in agreement with the structures found in the solid state by X-ray crystallography and found for analogous complexes as published previously [24].…”
Section: Resultssupporting
confidence: 89%
“…The bond lengths RuCl1 = 2.4066(8), Ru-Cl2 = 2.4181 (7), Ru-C1 = 1.834 (3), C1-O1 = 1.143 (4) and Ru-P = 2.3670 (7) are within the ranges observed in other complexes [24][25][26][27][28][29][30][31][32][33][34]. The bond length Ru-Cl2 = 2.4181 (7) is longer than RuCl1 = 2.4066 (8), this difference is probably due to the hydrogen bond involving Cl2 and CH 3 OH, as can be seen in Fig.…”
Section: Resultssupporting
confidence: 71%
“…The phenyl substituted dialkyl ketone 4-phenyl-2-butanone gets readily reduced. Reetz and Li have recently reported the use of p-cymene containing precursor [{(g 6 -C 10 H 14 )RuCl (l-Cl)} 2 ] in presence of BINOL-derived diphosphonites for extremely effective asymmetric hydrogen-transfer hydrogenation (from 2-propanol) of ketones, it is notable that these systems do not require ancillary diamine ligands [71]. In addition, Deng's and Noyori's group have earlier used the same precursor in presence of a chiral diamine for hydrogenation of ketones in either aqueous media using sodium formate or basic 2-propanol [72,73].…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%